Kandungan Fosfor dan Kalsium pada Tanah dan Biomassa Hutan Rawa Gambut (Studi Kasus di Wilayah HPH PT. Diamond Raya Timber, Bagan Siapi-api, Provinsi Riau) - I Istomo (Institut Pertanian Bogor (IPB University), 2006)
Research on the biomassa, distribution and content of P and Ca nutrients in the soil and biomass was conducted in a primary forest with peat thickness ranging between 2.5 to 6.5 m in the forest concession area (HPH) of PT. Diamond Raya Timber, Bagan Siapi-api, the Riau Province. The objective of the research was to obtain data on the content of P and Ca in the vegetation and peat soil layers at several levels of peat thickness. Research results showed that although vegetation biomass constituted only 6 % of the total biomass of vegetation and peat soil, contain of P nutrient as much as 37 % and Ca 28 % out of the total P or Ca nutrients occurring in vegetation and peat soil. Increasing of peat thickness because the total content of nutrients in the peat soil also increased, although the average content of nutrient per depth interval of 50 cm decreased. Increasing of peat thickness alse increased the content of P or Ca for tree stage vegetation, on the other hand, the content of P or Ca in herbs and shurbs, decreased. This phenomenon shows that on peat thickness more than 3 m only higher vegetation (trees vegetation) could survive properly. Contetnt of P or Ca nutrients occuring at above ground tree stage vegetation reach 64 % and 74 %. While for tree stage vegetation, the biggest nutrient content occurred in branches, nas follows 44 % foer P and 40 % for Ca. Pioneer trees species and lesser known timber in fact had the highest P and Ca elernent concentration. For the highest Ca elements were in timah-timah (Ilex bogoriensis- 14,02 g kg-1), milas (Parastemon urophyllum,13,72 kg-1) and suntai (Palaquium dasyphyllum; 13,13 g kg-1). While for P element of beringin (Ficus benyamina;20,1 g kg-1), punak (Tetramerista glabra; 1,91 g kg-1) and terentang (Camnosperma macrophylla; 1,59 g kg-1).